146 Efficacy and Safety of the Asenapine Transdermal Patch, HP-3070, for Schizophrenia: A Phase 3, Randomized, Placebo-Controlled, Inpatient Study. (April 2020) - Citrome, Leslie; Walling, David; Zeni, Courtney; Komaroff, Marina; Park, Alexandra
Abstract: Background: Asenapine is a 2nd-generation antipsychotic currently marketed as a sublingual (SL) tablet in the US for the treatment of schizophrenia. HP-3070, asenapine transdermal system, is a patch for treatment of schizophrenia in adults. Low- and high- HP-3070 doses deliver asenapine concentrations that are similar to SL asenapine 5 mg BID and 10 mg BID, respectively, but with fewer peak and trough fluctuations. Methods: In this Phase 3, randomized, double-blind, placebo (PBO)-controlled, 6-week inpatient study, adults with schizophrenia having baseline Positive and Negative Syndrome Scale (PANSS) total score ≥80 and Clinical Global Impression–Severity of Illness Scale (CGI-S) score ≥4 were randomized 1:1:1 to HP 3070 high-dose, HP-3070 low-dose, or PBO. The primary efficacy objective was Week 6 PANSS score change from baseline (CFB) vs PBO. The key secondary objective was Week 6 CGI-S CFB vs PBO. Safety assessments included treatment-emergent adverse events (TEAEs), laboratory results, vital signs, dermal safety, and extrapyramidal symptoms (EPS) assessments. Results: A total of 616 patients were randomized, with 486 patients completing the study. Discontinuation rates were 23.3%, 18.6%, and 21.4% for HP-3070 high-dose, HP-3070 low-dose, and PBO, respectively; withdrawal of consent and AEs were the most common reasons for discontinuation. Demographics and baseline characteristics were well-balanced among treatment groups. For PANSS total score, least squares mean (LSM) (standard error [SE]) estimates of the treatment comparison (HP-3070 vs PBO) for CFB at Week 6 were -4.8 (1.634; 95% CI: -8.06, -1.64; p=0.003) and -6.6 (1.630; 95% CI: 9.81, 3.40; p<0.001) for HP-3070 high- and low-dose, respectively. For CGI-S CFB at Week 6, LSM (SE) for the treatment comparison were 0.4 (0.100; 95% CI: 0.55, 0.16; p<0.001) for HP 3070 high-dose and 0.4 (0.099; 95% CI: 0.64, 0.25; p<0.001) for low-dose. No deaths or serious TEAEs related to study treatment occurred. The HP-3070 safety profile was consistent with SL asenapine. Incidence of TEAEs at the patch application site was higher for HP-3070 (14.2% high-dose, 15.2% low-dose) than for PBO (4.4%); most of these events were mild or moderate in severity. PBO patients had higher rates of psychiatric disorders (24.3% vs 15.7% and 17.6% for HP-3070 high- and low-dose, respectively), with insomnia and anxiety as most common. Study treatment discontinuations due to application site reactions or skin disorders were low (≤0.5%) across treatment groups. There was no marked mean CFB for vital signs or electrocardiogram parameters, nor treatment differences observed on EPS assessments. Conclusions: In this study, HP-3070 was efficacious, safe, and well-tolerated for treating schizophrenia in adults; both doses met primary and key secondary endpoints. As the first transdermal antipsychotic patch in the US, HP-3070 will provide patients a novel treatment option. Funding Acknowledgements: Funded by Noven Pharmaceuticals, Inc., a wholly-owned subsidiary of Hisamitsu Pharmaceutical Co.